The Effect of Firing Temperature on Water Absorption and Flexural Strength on The Preparation of Stoneware Ceramic (Coded-BL1P) - Sujana, G. Agus Permana Putra; Suardana, Putu; Nugroho, Totok (BULETIN FISIKA; Vol 20 No 1 (2019): BULETIN FISIKA, 2019)
It has been investigated the effect of firing temperature on water absorption and flexural strength in the manufacture of BL1P code stoneware ceramics. Ceramics are made in the form the test block bar with materials from of Borneo Clay Noodle, PRC Feldspar, Kaolin Belitung, Belitung Quartz, Ballclay Bantur, Bentonite, and Talk with a simple casting method. The block bar of the molds was burned at four temperature variations, i.e. 850, 900, 1000, and 1200 o C. From the results of measurements of it water absorption, it was found that the increase in firing temperature from 850 o C to 1200 o C showed a decrease in water absorption from 18.3% to 5.5%, while the measurement of it flexural strength showed an increase in flexural strength of 11.6 kg/cm 2 to 19.8 kg/cm 2 .